Tissues distribution of heavy metals and erythrocytes antioxidant status in rats exposed to Nigerian bonny light crude oil (2011)
The harmful effects of folkloric uses of Nigerian bonny light crude oil (BLCO) in ailments management may outweigh the expected beneficial effects. We investigated the levels of heavy metal concentrations in the tissues as well as the effect of BLCO on the antioxidant status of erythrocytes of rats after oral exposure to 0, 200 and 800 mg/kg BLCO for 7 days. Analysis of heavy metal concentrations in BLCO showed that Zn > Fe > Pb > Cu > Ni. The trend of accumulation of the metals in the tissues is blood—Fe > Pb >Zn whereas Cu and Ni levels were not affected; Liver—Ni > Zn > Fe > Cu > Pb and Testes—Ni > Cu > Pb > Zn > Fe. The order of concentration of the metals in the tissues is as follows: iron—blood > liver > testes; zinc—liver > blood > testes; lead—blood > liver > testes; copper—testes > liver > blood; nickel—liver > testes > blood. Activities of the antioxidant enzymes of erythrocytes such as superoxide dismutase, catalase, glutathione S-transferase and glutathione peroxidase increased significantly in a dose-dependent manner with significant elevation in hydrogen peroxide and malondialdehyde levels, whereas glutathione level was not significantly decreased in BLCO-treated animals. Collectively, the results showed that BLCO induces oxidative damage to erythrocytes of rats.